2019
DOI: 10.3389/fped.2019.00233
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Complex Relationship Between Tuberculosis and Other Infectious Diseases in Children

Abstract: Millions of children are exposed to tuberculosis (TB) each year, many of which become infected with Mycobacterium tuberculosis . Most children can immunologically contain or eradicate the organism without pathology developing. However, in a minority, the organism overcomes the immunological constraints, proliferates and causes TB disease. Each year a million children develop TB disease, with a quarter dying. While it is known that young children and those with immunodeficiencies are at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 243 publications
1
41
0
Order By: Relevance
“…Multiple studies have shown that viruses such as influenza, HIV, and measles can impair the ability of macrophages to contain mycobacterial growth, including Mycobacterium tuberculosis [26,27]. In a mouse model of influenza A and M. tuberculosis, co-infection resulted in enhanced mycobacterial growth in the lungs and decreased survival mediated by type I IFN signaling [28].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that viruses such as influenza, HIV, and measles can impair the ability of macrophages to contain mycobacterial growth, including Mycobacterium tuberculosis [26,27]. In a mouse model of influenza A and M. tuberculosis, co-infection resulted in enhanced mycobacterial growth in the lungs and decreased survival mediated by type I IFN signaling [28].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that viruses such as in uenza, HIV,and measles can impair the ability of macrophages to containmycobacterial growth, including Mycobacterium tuberculosis [18,19]. In a mouse model of in uenza A and M.tuberculosis, co-infection resulted in enhancedmycobacterial growth in the lungs and decreased survival mediatedby type I IFN signaling [20].Type I interferons also reduce theability of macrophages to respond to IFN-γ and control o ntracellular growth of M. tuberculosis [21].This child additionally had persistent lymphopenia, which is a riskfactor for severe tuberculosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is the dynamic balance between bacterial pathogenicity and the host immune system that determines the clinical presentation of TB disease. This balance is influenced by several factors including the infectious dose, virulence and persistence of the pathogen, host health and co-morbidities (HIV/AIDS, diabetes, and others), and the interplay between the innate and acquired immune system [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%